Modified Silica Adsorbent from Volcanic Ash for Cr(VI) Anionic Removal - Endang Tri Wahyuni; Roto Roto; Firda Ainun Nissa; Mudasir Mudasir; Nurul Hidayat Aprilita (Universitas Gadjah Mada, 2018)
In the present research, cetyltrymethyl ammonium bromide (CTAB)-modified silica from Kelud’s volcanic ash has been prepared and examined as adsorbent for removal of the hazardous Cr(VI) anion. The research was initiated with purification of SiO2 from the volcanic ash that was carried out by reacting the volcanic ash with NaOH powder at 900 °C for 2 h, followed by dissolving the ash to water at 100 °C, and then was acidified with HCl 1 M to form hydrogel. By calcination of the hydrogel, silica (SiO2) gel was obtained. The next step was modification of the silica with CTAB, that was performed by interacting the CTAB solution with the gel, in which the concentration of the CTAB was varied. Then the CTAB-modified silica samples were characterized by using FTIR, XRD, and SEM machines. The activity of the adsorbent was examined for adsorption of CrO4= in the solution. The results of the research demonstrate that the amorphous silica gel and the amorphous CTAB-modified silica have been obtained. The CTAB-modified silica was found to possess much higher ability in the adsorption of CrO4= anion, that was 48.90 mg/g, compared to that of the unmodified silica gel, as much 5.68 mg/g. These findings strongly prove that the negative surface of the CTAB-modified silica adsorbent has been successfully formed. Furthermore, it is also observed that increasing concentration of CTAB in SiO2-CTA can promote more effective adsorption of the CrO4= from the solution, but the further enlargement of the CTAB concentration leads to the adsorption decreased, and the highest adsorption was shown by CTAB-modified silica prepared with 0.10 mole of CTAB/1 mole SiO2.